1999
DOI: 10.1515/hf.1999.042
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability of Extractives in Sapwood and Heartwood from Scots Pine by Sapstain and White-Rot Fungi

Abstract: SummaryThe fungal degradation of lipophilic extractives in sapwood and heartwood from Scots pine (Pinus sylvestris) was studied. In sapwood, the white rot fungi,Bjerkanderasp. andFunalia trogii, removed higher amounts of extractives than the sapstain strains,Ophiostoma ainoaeandCeratocystis allantospora. Triglycerides, long chain fatty acids, steryl esters and waxes in pine sapwood were almost completely degraded by all the fungi. Sterols and resin acids were also extensively degraded by the white rot strains;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 12 publications
10
32
0
Order By: Relevance
“…A higher degradation rate was observed for Scots pine than for Norway spruce extractives, which was attributed to differences in the degradation of triglycerides (Josefsson et al 2006). Some studies reported a low efficiency in the removal of sterol esters (Chen et al 1994;Josefsson et al 2006) whereas other reports showed a significant conversion of these compounds by sapstain fungi (Gutiérrez et al 1999b;Martínez-Íñigo et al 1999). However, the Cartapip strain and related fungi seem to be unable to efficiently remove free sterols from hardwoods and resin acids from softwoods (Chen et al 1994;Dorado et al 2000a;Gutiérrez et al 1999b;Martínez-Íñigo et al 1999), even though, a significant decrease in free sterols (up to 60%) was reported by Su et al (2004) to be caused by some newly screened fungal strains.…”
Section: A Sapstain Fungimentioning
confidence: 98%
See 2 more Smart Citations
“…A higher degradation rate was observed for Scots pine than for Norway spruce extractives, which was attributed to differences in the degradation of triglycerides (Josefsson et al 2006). Some studies reported a low efficiency in the removal of sterol esters (Chen et al 1994;Josefsson et al 2006) whereas other reports showed a significant conversion of these compounds by sapstain fungi (Gutiérrez et al 1999b;Martínez-Íñigo et al 1999). However, the Cartapip strain and related fungi seem to be unable to efficiently remove free sterols from hardwoods and resin acids from softwoods (Chen et al 1994;Dorado et al 2000a;Gutiérrez et al 1999b;Martínez-Íñigo et al 1999), even though, a significant decrease in free sterols (up to 60%) was reported by Su et al (2004) to be caused by some newly screened fungal strains.…”
Section: A Sapstain Fungimentioning
confidence: 98%
“…The capabilities of some Ophiostoma species and other sapstain fungi in removing different classes of lipophilic extractives were assessed for both softwoods (Table 17.1) and hardwoods (Table 17.2). Among others, the effectiveness of these fungi to degrade triglycerides and free fatty acids was demonstrated in several independent studies using different types of wood Brush et al 1994;Dorado et al 2000a;Gutiérrez et al 1999b;Josefsson et al 2006;Martínez-Íñigo et al 1999;Rocheleau et al 1999). A higher degradation rate was observed for Scots pine than for Norway spruce extractives, which was attributed to differences in the degradation of triglycerides (Josefsson et al 2006).…”
Section: A Sapstain Fungimentioning
confidence: 98%
See 1 more Smart Citation
“…Various phenolic compounds in wood extracts have been reported to inhibit fungi (CHERDCHIM, 2010;MARTÍNEZ-IÑIGO et al, 1999;LEONOWICZ et al, 2001), such as 3-Methoxy-4-hydroxybenzoic acid and 4-Hydroxy cinnamic acid, active against the white-rot Pleurotuso streatus and Trametes versicolor (CHERDCHIM, 2010). Here, we demonstrated clear negative effects of H. brasiliensis extracts on fungal growth (Figures 1 and 2).…”
Section: Gc-ms Identification Of Compounds In H Brasiliensis Extractsmentioning
confidence: 99%
“…These fungi live on sugars, lipids and resins present as storage and protective materials within ray parenchyma and resin canals of the sapwood (Martinez-Inigo et al 1999, Fleet et al 2001. Usually, they cause little or no destruction and strength loss to the wood but the unsightly staining represents loss of value for production of solid wooden objects as well as for paper and cardboard production (Vanneste et al 2002).…”
Section: Biological Control After Fellingmentioning
confidence: 99%